The top performer: Towards optimized parameters for reduced graphene oxide uniformity by spin coating. (2nd May 2021) - Reiner‐Rozman, Ciril; Hasler, Roger; Andersson, Jakob; Rodrigues, Teresa; Bozdogan, Anil; Bintinger, Johannes; Aspermair, Patrik
Abstract: Reduced graphene oxide has shown great potential for the fabrication of different electronic devices, especially biosensors and electric circuits. It allows the usage of simple deposition techniques such as drop casting or spin coating of graphene oxide solutions with a subsequent chemical, electrochemical, and/or thermal reduction to reduced graphene oxide. However, the utilized deposition strategy requires a defined protocol that ensures reproducibility. A study on a range of concentrations of GO and spin coating parameters is presented, aiming at the most uniform layers consisting of only single and double sheets for the application in electronic devices. The effect of film deposition on morphological parameters like the number of layers, overlaps, and surface coverage as well as the influence on electronic properties such as baseline stability and the transfer characteristics for the application as an electrolyte gated field‐effect transistor (EG‐FET) are shown. Best film characteristics and electronic properties are achieved by using a GO concentration of 214 μg/mL applied via spin coating with 1800 rpm, after surface modification with adhesive layer.